The effects of varying number of seeds per hill on the yield of peanuts - Millama, Godofreda Aboy; Lagman, Myrna V. (Tacloban City Management and Technology Program, University of the Philippines College of Tacloban, 1981)
The effect on the yield of peanuts was determined based on the number of peanut seeds planted per hill in 336 square meters "experimental lot" subdivided into 6 subplots. Subplots with four seeds per hill exhibited a highest average yield. Meanwhile, the varying number of seeds planted per hill and the rate of fertilizer, did not affect the length of pods in peanuts. Other factors that impacted the yield of peanuts were environmental factors, maturity of peanuts, management and cultivation, soils, location, insect pests and disease.
Undergraduate thesis (Bachelor of Science in Agri-Business)--University of the Philippines College of Tacloban, March 1981.
Keywords: Peanuts -- Yields; Peanuts -- Field experiments